Peran Notaris Terhadap Perlindungan Hukum Investor dalam Securities Crowdfunding pada Usaha Kecil dan Menengah (UKM) - Apsari, Kirana; Bagiastra, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 03 (2024)DO - 10.24843/AC.2024.v09.i03.p11, 2024)
The research on the Role of Notaries in Investor’s Legal Protection in Securities Crowdfunding for SMEs aims to provide a comprehensive understanding of the legal protection that can be offered to investors based on the roles and responsibilities of notaries, and how notarial legal education can enhance investor confidence. This study employs normative legal research methods with a legislative approach and legal concept analysis. Primary legal sources include legislation, supported by secondary legal materials such as legal books, journals, and related articles. The findings of this research indicate that notaries play a role in protecting investors in SME SCF through the creation of authentic deeds and the obligation to recognize beneficial ownership in deed creation, which is part of efforts to prevent money laundering. Additionally, the role of notaries in providing legal education to enhance investor confidence in SME SCF involves offering guidance on debt acknowledgment deeds to prevent legal consequences arising from misunderstandings about legal actions.